Processing of a Novel Zn Alloy Micro-Tube for Biodegradable Vascular Stent Application. Issue 9 (September 2016) - Wang, Chang; Yu, Zhentao; Cui, Yajun; Zhang, Yafeng; Yu, Sen; Qu, Gongqi; Gong, Haibo
Abstract : In recent years, zinc based alloys as a new biodegradable metal material aroused intensive interests. However, the processing of Zn alloys micro-tubes (named slender-diameter and thin-walled tubes) is very difficult due to their HCP crystal structure and unfavorable mechanical properties. This study aimed to develop a novel technique to produce micro-tube of Zn alloy with good performance for biodegradable vascular stent application. In the present work, a processing method that combined drilling, cold rolling and optimized drawing was proposed to produce the novel Zn–5Mg–1Fe (wt%) alloy micro-tubes. The micro-tube with outer diameter of 2.5 mm and thickness of 130 µm was fabricated by this method and its dimension errors are within 10 µm. The micro-tube exhibits a fine and homogeneous microstructure, and the ultimate tensile strength and ductility are more than 220 MPa and 20% respectively. In addition, the micro-tube and stents of Zn alloy exhibit superior in vitro corrosion and expansion performance. It could be concluded that the novel Zn alloy micro-tube fabricated by above method might be a promising candidate material for biodegradable stent.